Effect of Storage Media and Sterilization Method on Shear Bond Strength of Composite to Enamel of Extracted Teeth - Alireza Boruziniat; Nasrin Danaifard; Mahshid Gifani; Narjes Hakimi (Mashhad University of Medical Sciences, 2017)
Aim: To evaluate the effect of storage media and autoclaving on shear bond strength of composite to enamel. Materials and Methods: 100 human premolars were randomly divided into ten groups of ten as follows: C: freshly extracted teeth. A: Autoclaved freshly extracted teeth. CH-6: 6 month storage in 0.5 % chloramine T. CA-6: 6 month storage in 0.5 % chloramine T + autoclaving. T-6: 6 month storage in 0.04 % thymol. TA-6: 6 month storage in 0.4% thymol + autoclaving. Ch-12:12 month storage in 0.5 % chloramine T. CA-12: 12 month storage in 0.5 % chloramine T + autoclaving. T-12: 12 month storage in 0.4% thymol. TA-12:12 month storage in 0.4% thymol + autoclaving. One composite cylinder was bonded on each specimen for evaluation of shear bond strength (SBS) and failure modes. Data were analyzed using three-way ANOVA, Tukey's post hoc and Chi square tests and the level of significance was set  at P= 0.05. Results: Autoclaving and storage media had no significant effect on SBS (P-value = 0.818 for storage media and P-value = 0.221 for autoclaving). However, storage duration significantly changed SBS (P-value = 0.00). There were no correlations among the variables (P-value > 0.05). Storage media and duration had no significant effect on failure modes (P-value > 0.05), but autoclaving significantly increased cohesive failure of enamel (P-value =0.039). Conclusion: Storage of teeth in chloramine T and thymol had no significant effect on bond strength to enamel. Although autoclaving of specimens may not alter bond strength, it can significantly increase the cohesive failure of enamel.